2007
DOI: 10.1007/s00441-007-0466-7
|View full text |Cite
|
Sign up to set email alerts
|

TGF-beta in neural stem cells and in tumors of the central nervous system

Abstract: Mechanisms that regulate neural stem cell activity in the adult brain are tightly coordinated. They provide new neurons and glia in regions associated with high cellular and functional plasticity, after injury, or during neurodegeneration. Because of the proliferative and plastic potential of neural stem cells, they are currently thought to escape their physiological control mechanisms and transform to cancer stem cells. Signals provided by proteins of the transforming growth factor (TGF)-beta family might rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 201 publications
(245 reference statements)
4
93
0
Order By: Relevance
“…A role for TGFb1 in glial differentiation is consistent with its being a member of a superfamily of growth factors known to produce a diverse range of biological effects in the developing CNS, including NSC expansion and fate determination [38][39][40]. Its role is also consistent with the observation that conditioned medium from hMSCs increased oligodendrogenesis by rNSCs incubated in medium containing 10% FBS [41,42].…”
Section: Discussionsupporting
confidence: 66%
“…A role for TGFb1 in glial differentiation is consistent with its being a member of a superfamily of growth factors known to produce a diverse range of biological effects in the developing CNS, including NSC expansion and fate determination [38][39][40]. Its role is also consistent with the observation that conditioned medium from hMSCs increased oligodendrogenesis by rNSCs incubated in medium containing 10% FBS [41,42].…”
Section: Discussionsupporting
confidence: 66%
“…Subsequent in vitro experiments using quail neural crest cell demonstrated that TGF-β inhibits proliferation of neural crest cells while neurogenesis increased significantly in the presence of TGF-β (Zhang et al, 1997). Subsequent experiments using brains supported an inhibitory role of TGF-βs on neuronal stem cell proliferation (Aigner & Bogdahn, 2008). TGF-β had an antimitotic effect on progenitors and increased expression of neuronal markers in hippocampal and cortical primary cell cultures of developing mouse (Vogel et al, 2010).…”
Section: Neuronal Differentiation and Survivalmentioning
confidence: 94%
“…In fact, they develop mechanisms that change the anti-proliferative influence of TGF-β into oncogenic cues. Thus, TGF-β is involved in tumor progression (Aigner & Bogdahn, 2008). The dominant hypothesis of TGF-β's pathogenetic association with malignant transformation has been predicated upon acquisition of resistance to its growth inhibitory effects.…”
Section: The Role Of Tgf-βs In Brain Tumor Formationmentioning
confidence: 99%
“…The TGFβ superfamily consists of more than 100 different proteins, such as activins and inhibins, bone morphogenetic proteins (BMP), veg-1, the Drosophila decapentaplegic complex, and Mullerian-inhibiting substance. Thus far, more than 40 members of this superfamily have been described in mammals 38,39 as being involved in various physiological and pathophysiological processes of the brain. All three isoforms TGFβ1, TGFβ2 and TGFβ3 are expressed in neurons and glial cells 36 .…”
Section: Molecular Pathways and Tumorigenesismentioning
confidence: 99%
“…A similar effect on neurogenesis occurs during normal mammalian CNS development, when TGFβ has been reported to inhibit neural stem cell proliferation. In cancer, however, this TGFβ mediated cell growth control seems to be bypassed 39 . Resistance to growth inhibition can be detected in malignant glioma cells with functionally active TGFβ receptors 53 .…”
Section: Molecular Pathways and Tumorigenesismentioning
confidence: 99%